Deconstructing Ta’dzim Culture: The Implementation of Sayyidah Aisyah’s Critical Pedagogy to Foster Discursive Logic Among Santri - Siti Nur Haliza; Moh. Amiril Mukminin (Assyfa Journal of Islamic Studies, 2025)
In the current era of information disruption and pluralistic discourse, santri (Islamic students) desperately need discursive reasoning skills and critical awareness to interact argumentatively in the public sphere. Critical pedagogy-based teaching, which prioritizes dialogue, clarification, and intellectual courage, is seen as an effective strategy for transforming traditional learning into a more participatory one. While research on ta’dzim has tended to focus on symbolic obedience, this article evaluates the shift in meaning from epistemic respect to passive obedience, which hinders students' logic. The impact of this rigid hierarchical culture is evaluated on the reduction of critical reasoning skills and the development of students' cognitive dimensions and reflective awareness (conscientization). This research aims to deconstruct ta’dzim culture by integrating Sayyidah Aisyah's (r.a.) critical pedagogical model into the Islamic boarding school education system. Using a qualitative approach with a literature review method and Critical Discourse Analysis (CDA) techniques, this study analyzes power relations in religious pedagogical texts through data reduction and categorization. The findings indicate that Sayyidah Aisyah's pedagogy has a positive impact in the form of active-discursive ta'dzim (religious understanding), where tashīḥ (clarification) and dialectical dialogue serve as scaffolding to enhance the intellectual agency of students. The findings conclude that the authority of the kiai (Islamic cleric) is not diminished by criticism; rather, the revitalization of knowledge through discussion strengthens the students' morals and epistemic responsibility. Consequently, this reconstruction enables Islamic boarding schools (pesantren) to become progressive learning spaces without abandoning their traditional roots.